Study Travel Time in the Movement of Passengers and Baggage at the Arrival Station of Sultan Hasanuddin International Airport Makassar - F Sabur (AVIA, 2020)
Airport provides facilities for services to aircraft, passengers, and goods. One of the activities at the airport is handling your luggage. At some particular time, especially in crowded flight, a passenger still faces delays in receiving baggage at the arrival terminal. The purpose of the research is to know the travel time difference and the factors that influence the travel timedifferences in the movement of passengers and baggage at the arrival terminal of Sultan Hasanuddin International Airport of Makassar. The type of research is a correlation study, using primary data in the form of data direct field measurements as well as secondary data from the monthly reports-MATSC Support Operations Division Aeronautical Information Service in theform of fixed flight schedules and Side Air Operations Division in the form of data movement apron. Processing the data is by using SPSS version 18:00 The findings is: the smallest time difference between the passenger and baggage occurs when using the bus, followed a garbarata and the greatest difference in time when walking, so that it can be concluded that the use of buses more effective in reducing delays in receiving the baggage at the arrival terminal of International Airport Sultan Hasanuddin of Makassar